PENDIDIKAN ISLAM DIERA REVOLUSI INDUSTRI 4.0 - MUSTAFA, MA (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2020)
Islamic education has entered a new chapter in its long journey. Namely the era of digitalization and industrial acceleration that has penetrated in all aspects of life. Uniquely, Islamic education is a little too late to say that it has not at all made adjustments to the new style which prioritizes accelerated access, automation, connectivity and efficiency that is completely controlled with the internet system. Strong pressure is increasingly felt when the outside world is increasingly innovating in its latest findings, Islamic Education seeks to innovate and make significant changes. Islamic education in addition to being an obligation, is absolutely needed by every Muslim child for the sake of his existence. Especially when entering the era of globalization which is full of challenges. Islamic education which emphasizes aspects of spiritual intelligence has a format for maintaining, utilizing, and developing human nature in anticipating spiritual crises in the era of globalization.